2008
DOI: 10.1002/zoo.20174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of knowledge gain between interpretive and fact‐only presentations at an animal training session: an exploratory study

Abstract: Zoos and aquariums have recognized the importance of integrating living collections with personally delivered interpretation. One way for zoos to accomplish this is by conducting public animal training sessions accompanied by personal interpretation. Many institutions offer these types of interactions, but the term "interpretation" is used loosely and without clear definition. This exploratory study compared knowledge gain of individual students in three different fifth grade school groups visiting the Potter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
2
25
1
Order By: Relevance
“…Thus, it is possible that seeing primates interacting with human scientists could have a negative effect on public understanding of primate science and conservation, rather than the desired positive effect. Animal training demonstrations in zoos, however, have been shown to have a positive effect on visitor learning [7], [8], but we cannot assume this is true of live scientific demonstrations with primates without empirical evidence.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, it is possible that seeing primates interacting with human scientists could have a negative effect on public understanding of primate science and conservation, rather than the desired positive effect. Animal training demonstrations in zoos, however, have been shown to have a positive effect on visitor learning [7], [8], but we cannot assume this is true of live scientific demonstrations with primates without empirical evidence.…”
Section: Introductionmentioning
confidence: 96%
“…The design of RCAA, for example, provided distinct areas for ape training demonstrations that likely enhanced the educational impact of the exhibit. Interpretive presentations by zoo staff or volunteers have been shown to be more effective at producing knowledge gain than facts alone (Visscher, Snider and Stoep 2009) and may be necessary to capture, focus, and fully engage the attention of zoo visitors before an appreciable impact on learning is obtained (Bitgood 2010). A range of factors including identity-related motivations influence visitor learning (Falk and Storksdieck 2010), and future zoo exhibit POEs may therefore benefit by including more nuanced analyses that link changes in zoo-visitor knowledge to design features.…”
Section: Discussionmentioning
confidence: 98%
“…The broader impacts of even small shifts in visitor attitude in the right direction could be significant if one considers that more than 175 million people visit zoos and aquariums each year (Association of Zoos and Aquariums 2011). To achieve maximum conservation education impact, it is important that the passive benefits afforded by superbly designed ape exhibits and educational graphics are complemented and strengthened by active interpretation and programming (Stoinski et al 2001;Visscher, Snider and Stoep 2009;Wagner et al 2009). …”
mentioning
confidence: 99%
“…Studies have shown that live interpretation results in larger learning gains than other explanatory methods, such as static text labels [22,26]. This effect is augmented when interpretation incorporates visitor contributions to dialogue, compared to more lecture-like interactions [42]. In addition to speaking with visitors, interpreters must also manage an entire system of interactions involving visitors, technology, tools, exhibits, and educational content.…”
Section: Background and Related Work 21 Interpretation In Isismentioning
confidence: 98%